POSSIBILITIES AND LIMITATIONS OF THE MAGNETIC CONTROL OF THE CAST IRON CASTINGS STRUCTURE (Review) - S. G. Sandomirskij (Литьë и металлургия)
The recommendations on application of technical means of control are given.